2003
DOI: 10.1002/j.2162-6057.2003.tb00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Creativity of university students: What is the impact of field and year of study?

Abstract: There is a long‐lasting dispute about development of students' creativity in the course of their university education. Both the duration and major field of study may represent the educational effects. To address the issue, the present study collected data (N = 859) from a series of surveys of students in Hong Kong to clarify educational effects by controlling a number of background characteristics and prior scores on creativity. Apart from measuring self‐reported creative traits and creative products, it measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
2
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 35 publications
1
32
2
10
Order By: Relevance
“…For instance, to examine college students' creativity and its relationship with their academic achievement, Cheung, Rudowicz, Yue, and Kwan (2003) required participants to complete five divergent thinking tasks, which consisted of the Alternate Uses Test (Christensen, Guilford, Merrifield, & Wilson, 1960), two tasks adapted from Sternberg (1990) and Sternberg and Lubart's (1992) work, and two from Wallach and Kogan (1965) creativity tests. Armstrong (2012) assessed different aspects of creativity by a single product improvement task selected from TTCT, an updated Remote Association Task, a creative problem solving task adapted from Redmond, Mumford, and Teach (1993), and a self-report Lifetime Creativity Scales (LCS; Richards, Kinney, Benet, & Merzel, 1988).…”
Section: Review Of Research Methodologies and Methodsmentioning
confidence: 99%
“…For instance, to examine college students' creativity and its relationship with their academic achievement, Cheung, Rudowicz, Yue, and Kwan (2003) required participants to complete five divergent thinking tasks, which consisted of the Alternate Uses Test (Christensen, Guilford, Merrifield, & Wilson, 1960), two tasks adapted from Sternberg (1990) and Sternberg and Lubart's (1992) work, and two from Wallach and Kogan (1965) creativity tests. Armstrong (2012) assessed different aspects of creativity by a single product improvement task selected from TTCT, an updated Remote Association Task, a creative problem solving task adapted from Redmond, Mumford, and Teach (1993), and a self-report Lifetime Creativity Scales (LCS; Richards, Kinney, Benet, & Merzel, 1988).…”
Section: Review Of Research Methodologies and Methodsmentioning
confidence: 99%
“…Several studies concluded that creative thinking is declining both over time (Kim 2011) and with age among adults (McCrae et al 1987) and students (Cheung et al 2003). While studies show that creativity significantly decreases over time, authors investigating the development of creativity within adults also find the phenomenon of latent creativity (Evans 1967;Yong 1994;Herne et al 2013) -creativity that exists in an unconscious or dormant form but has the potential to be expressed.…”
Section: A Case Study: Prototyping Workhop For Stimulating Latent Crmentioning
confidence: 99%
“…Por otra parte, investigadores de diferentes países ya habían manifiestado la reducida contribución en el sistema educativo universitario del desarrollo de la creatividad. (Cheung et al, 2003;Soler, 2003;Rinaudo y Donolo, 1999 Algunos estudiantes inicialmente manifiestan sentirse muy poco creativos y se muestran cerrados a la generación de nuevas ideas. Guilford (1986), uno de los primeros estudiosos sobre la materia, ya manifestó que la creatividad está presente en distintos niveles en todos los individuos.…”
Section: Proceso De Aprendizaje De La Creatividad Como Competenciaunclassified